Incorporating practitioner inquiry into an online professional development program: the Prime Online experience. Issue 2 (15th March 2017) - Dana, Nancy Fichtman; Pape, Stephen J.; Griffin, Cynthia C.; Prosser, Sherri Kay
Abstract : Engagement in practitioner inquiry by classroom teachers is a promising mechanism for teacher professional learning. While much has been learned about the positive role inquiry can play in traditional professional development efforts, we know less about the impact of inquiry in a rapidly advancing technological age that includes the proliferation of online professional development institutes and programs. The purpose of this article is to explore the role of inquiry in online professional development by providing a detailed description of a year-long program called Prime Online. Supported by US federal funding, this program was designed to help teachers develop the mathematics content and pedagogical content knowledge necessary to implement research-based practices in inclusive elementary classrooms within a framework of practitioner inquiry. A detailed description of this program is presented followed by an examination of the inquiry projects completed by the participants. Implications of this effort for teacher learning and online professional development endeavors are offered.